Intravital Imaging Reveals Dynamics of Lymphangiogenesis and Valvulogenesis - Kang, Gyeong Jin (Sci Rep, 2016)
Lymphatic research signifies a field of rapid progression in recent years. Though lymphatic dysfunction has been found in a myriad of disorders, to date, few effective treatments are available for lymphatic diseases. It is therefore urgent to develop new experimental approaches and therapeutic protocols. The cornea offers an ideal site for lymphatic research due to its transparent nature, accessible location, and lymphatic-free but –inducible features. Moreover, we have recently discovered that corneal lymphatic vessels develop luminal valves as lymphangiogenesis proceeds. This tissue thus provides an optimal tool to study both lymphangiogenesis and valvulogenesis upon a pathological insult. In this paper, we show that the modified Prox-1-GFP mice carrying wildtype C57BL/6 background provide a valuable tool for intravital imaging of corneal lymphatic vessels and valves and can be used to study pathological lymphangiogenesis induced by various insults. Further, we demonstrate the multifaceted dynamics of lymphangiogenesis and valvulogenesis associated with transplantation, from the initiation to regression phases, and report several novel and critical phenomena and mechanisms that cannot be detected by conventional ex vivo approaches. Further investigation holds the great potential for divulging new mechanisms and therapeutic strategies for lymphangiogenesis and lymphangiogenesis-related diseases at various stages and inside or outside the eye.